Klasifikasi Biaya Berdasarkan Produksi Dan Perannya Terhadap Goal Perusahaan - Fauziah Nursya’bani Fadillah (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This article reviews the Classification of Costs based on Production and its role on Company Goals, where the classification of costs based on production includes: Raw material costs (materials), direct labor costs (BTKL) & factory overhead costs (BOP), therefore in this article will review these three costs that have a role or influence on company goals or not. This article is a Management Accounting literature study. The writing of this article aims to build a hypothesis of influence between variables to be used in further research. The results of this literature review article are: 1) Raw Material Costs affect the Company's Goal; 2) Direct Labor Costs affect the Company's Goal; and 3) Factory Overhead Costs affect the Company's Goal